Sickle cell leg ulcer successfully managed by hyperbaric oxygen: a case report - Alshurafa, Awni; Alkhatib, Mohammed; Abu-Tineh, Mohammad; Yassin, Mohamed A. (Frontiers in Medicine, 2023)
Sickle-cell leg ulcers (SCLUs) are usually chronic, painful, and devastating complications of sickle-cell disease. Skin vaso-occlusion with compromised blood flow, chronic inflammation, and endothelial dysfunction is thought to be the underlying mechanism. It is usually slow to heal and it may become chronic and superinfected. Management of SCLUs is usually challenging and requires a multidisciplinary team. There are multiple systemic and local therapies have been tried in SCLU treatment. However, the outcome is variable: currently, there are no official recommendations for the best effective treatment. Herein, we report a 34-year-old male patient with non-transfusion dependent sickle cell disease who was suffering from chronic left ankle ulcer and was successfully managed with hyperbaric oxygen therapy which resulted in complete resolution of this devastating complication.